ANALISIS POSTUR KERJA DAN KELUHAN MUSCULOSKELETAL DISORDERS (MSDS) PADA PETANI(STUDI LITERATURE RIVIEW) - Cindy Yunika Safithry; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Musculoskeletal disorders (MSDs) are health problems involving the joints, muscles, tendons, skeleton, cartilage, ligaments and nerves. The level of MSDs from the mildest to the most severe will interfere with concentration at work, cause fatigue and will ultimately reduce productivity. The agricultural sector is one of the jobs that has a potential risk of musculoskeletal disorders that have an impact on health related to their work which can cause several diseases and permanent disabilities. This study aims to determine the relationship between work posture and musculoskeletal disorders (MSDs) in farmers. This research is a research in the form of Literature Review. Researchers conducted searches on several search engines including: Google Scholar, Pubmed using the keywords "Working Posture" AND "Muscoluskeletal Disorders Complaints" AND "Farmers". Results: The articles used in this study were 8 articles that met the study requirements and criteria. The results showed that the cause of musculoskeletal disorders (MSDs) in farmers was work postures that were not ergonomic. Work posture is one of the factors causing MSDs where musculoskeletal complaints or MSDs are in the form of pain in the joints, ligaments, cartilage, skeleton and nerves. The emergence of these disorders causes a lack of concentration when working, fatigue and decreased productivity. Based on research conducted in a literature review, it can be concluded that there is a relationship between work posture and complaints of musculoskeletal disorders (MSDs) in farmers.